The Power of Interpersonal Communication Skill in Enhancing Service Provision - Febrianita, Roziana; Hardjati, Susi (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2019)
One of interpersonal soft skill is a skill of interpersonal communication; that is the focus of this research. The purpose of this paper are defined in two parts. First, to explore the interpersonal communication skills of the educational staff. Second, to recognize the power of this interpersonal communication. The research of this paper has been studied by means of qualitative method. The approach of this study is a sequences of in-depth interviews with 4 informants of each faculty with A credit for accreditation examination result. This research result finds that there are 3 interpersonal communication skills of educational staff area. Secondly, there are power of the interpersonal communication skill which have made improvement to service providing in the work unit. The results of this research also explain whether maintaining interpersonal relationship enhances the service providing.